Aktivitas Antibakteri Ekstrak Daun Sirsak (Annona muricata L.) Terhadap Pertumbuhan Bakteri Pseudomonas aeruginosa Secara In Vitro (ANTIBACTERIAL ACTIVITY OF SOURSOP (ANNONA MURICATA) LEAF EXTRACT ON GROWTH OF BACTERIA PSEUDOMONAS AERUGINOSA IN VITRO) - Fikri, Faisal; Rahmaningtyas, Imas Hapsari; Prastiya, Ragil Angga; Purnama, Muhammad Thohawi Elziyad (Jurnal Veteriner, 2019)
The aim of this study was to measure antibacterial activity of soursop leaf extract (Annona muricata L.) on bacterial growth inhibition of Pseudomonas aeruginosa by diffuse disc method. The result of the inhibition zone was analyzed using Analysis of Variance and followed using Duncan test, to show highly significantly different (p<0.01). The inhibition number of negative control (C-) was 0.00e±0.00 and the positive control (C+) was 31.31a±0.57. The result of concentration 1 (T1) was 14.49b±4.96; concentration 2 (T2) 8.98c±1.29; concentration 3 (T3) 5.84cd±1.85; concentration 4 (T4) 5.56cd±1.58; concentration 5 (T5) 2.85de±0.28; concentration 6 (T6) 2.98de±0.53; concentration 7 (T7) 2.82de±1.59; concentration 8 (T8) 2.41de±1.10; concentration 9 (T9) 2.20de±0.34; concentration 10 (T10) 1.10e±0.19; and concentration 11 (T11) 0.00e±0.00. The increase of soursop leaf extract concentration showed high inhibition diameter of bacterial growth. It concluded that soursop leaf extract have an antibacterial activity to inhibit P. aeruginosa growth with Minimal Inhibitory Concentration (MIC) 125 ppm.